Synthesis of novel olefin complexes of palladium(0) bearing monodentate NHC, phosphine and isocyanide spectator ligands. (1st April 2018) - Canovese, L.; Visentin, F.; Scattolin, T.; Santo, C.; Bertolasi, V.
Graphical abstract: We have prepared by one-pot synthesis and characterized by standard spectroscopic methods and SC-XRD seventeen new bis-NHC, mixed NHC–phosphines or NHC–isocyanides Pd(0) olefin complexes. We tried to validate our results by a computational study in order to establish the thermodynamic and kinetic conditions governing the mutual distribution of isomers. The rate of the exchange reaction between not particularly encumbered olefins was determined by conventional UV–Vis technique. Abstract: We have synthesized and characterized seventeen new bis-NHC, mixed NHC–phosphines or NHC–isocyanides Pd(0) olefin complexes that can potentially act as catalysts. The complexes were characterized by standard spectroscopic methods and elemental analysis and in two cases by SC-XRD technique. We have analyzed with particular care the thermodynamic and kinetic conditions governing the one-pot synthesis of the mixed complexes. In this respect we tried to validate our results by a dedicated computational study on the mutual distribution of the isomers that could be potentially formed. However, the computational result is not clear-cut owing to the not significant value of the calculated ΔG0 . Finally, in one case we have measured the rate of the exchange reaction between not particularly encumbered olefins.